Minimum threshold of near visual acuity of different correlated colour temperature in presbyopia / Siti Hajar Aida Samsuri - Samsuri, Siti Hajar Aida (Faculty of Health Sciences, 2015)
Introduction: The correlated colour temperature (CCT) of light is important factor that can affect near visual acuity (VA) in presbyopia. Within the normal near VA, it is possible that under different level of CCT of light, the minimum threshold acuity that can be achieved in presbyopia could be different compared to other ages. Objective: To determine the minimum threshold of near VA that can be achieved by presbyopia under different level of CCT using 2856 K, 4100 K and 6500 K of light and whether there is any difference of minimum threshold of near VA between three levels of CCT light. Materials and methods: This study involved subject aged between 35-65 years old (3 male, 11 female) with mean refractive error of -0.75DS and mean addition power of +2.04 DS. The subject was asked to read the letter acuity using Early Treatment Diabetic Retinopathy Screening (ETDRS) chart under three different levels of CCT light which are 2856 K, 4100 K and 6500 K. All the testing was done in the light booth (GTI LITE MODEL CMB 3064). For each CCT light, it required at least one day gap. Results: The mean of minimum threshold of near VA in 6500 K have highest mean value compared to 2856 K and 4100 K. The result from repeated measure ANOVA showed there was no statistically significant difference between the means of minimum threshold of near visual acuity that can be achieved by presbyopia and different level of CCT of light (p > 0.05) Conclusion: The highest CCT light 6500 K give better mean minimum of threshold near VA (logMAR) compared to 4100 K and 2856 K based on the mean result of minimum threshold of near VA (logMAR).